Ekstraksi dan Karakterisasi Pektin dari Limbah Kulit Pisang Ambon (Musa paradisiaca var. sapientum L.) - Sindi Idriana Tasya; Romy Dwipa Yamesa Away (Lembaga Yasin AlSys, 2025)
The underutilization of banana peels, which are often regarded as agricultural waste, serves as the basis for this study, given their actual potential as a natural biopolymer source rich in cellulose, hemicellulose, pectin, lignin, and protein. This research aims to explore the potential use of banana peel waste as a raw material for pectin production, with the dual objective of mitigating environmental problems and promoting the development of value-added materials. The method employed involved pectin extraction from banana peel powder using hydrochloric acid (HCl). The results indicated that the extracted pectin constituted 3.96% of the banana peel powder by weight and demonstrated gelling ability. The extracted pectin had an equivalent weight of 4166.66 mg, a methoxyl content of 6.94% classified as low methoxyl pectin (LMP), a degree of esterification of 90.26%, categorizing it as high ester pectin, and a galacturonic acid content of 43.65%. According to the quality parameters established by the International Pectin Producers Association (IPPA), the extracted pectin was of reasonably high purity. These findings suggest that banana peels have significant potential as an environmentally friendly and industrially applicable alternative source of pectin.